2021
DOI: 10.3390/molecules26113297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water and Ethanol Extracts from Hericium erinaceus Solid-State Fermented Wheat Product on the Protection and Repair of Brain Cells in Zebrafish Embryos

Abstract: Extracts from Hericium erinaceus can cause neural cells to produce nerve growth factor (NGF) and protect against neuron death. The objective of this study was to evaluate the effects of ethanol and hot water extracts from H. erinaceus solid-state fermented wheat product on the brain cells of zebrafish embryos in both pre-dosing protection mode and post-dosing repair mode. The results showed that 1% ethanol could effectively promote zebrafish embryo brain cell death. Both 200 ppm of ethanol and water extracts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(63 reference statements)
0
5
1
Order By: Relevance
“…The hot water extraction method has been widely used to extract bioactive polysaccharides from G. frondosa, and it 7 International Journal of Food Science was first employed in the 1980s [31]. This method has also been used to extract polysaccharides from fungal-fermented grains in many studies [32,33]. In this study, we used this method to extract polysaccharides from G. frondosa mycelium and polysaccharides from G. frondosa-fermented wheat products.…”
Section: Discussionmentioning
confidence: 99%
“…The hot water extraction method has been widely used to extract bioactive polysaccharides from G. frondosa, and it 7 International Journal of Food Science was first employed in the 1980s [31]. This method has also been used to extract polysaccharides from fungal-fermented grains in many studies [32,33]. In this study, we used this method to extract polysaccharides from G. frondosa mycelium and polysaccharides from G. frondosa-fermented wheat products.…”
Section: Discussionmentioning
confidence: 99%
“…Following the method outlined by Sun et al [14], Hericium erinaceus was cultured on PDA at a constant temperature of 25 • C. Once the mycelium was grown, three pieces of 1 cm 2 Hericium erinaceus were taken and placed in the pre-activation solution (composed of 5% glucose, 0.1% yeast extract, 0.05% dipotassium hydrogen phosphate, 0.05% magnesium sulfate, and 150 mL RO water), where they were cultivated at a constant temperature of 25 • C and a rotation speed of 150 rpm for 7 days.…”
Section: Hericium Erinaceus Solid-state Fermentation 2101 Pre-activat...mentioning
confidence: 99%
“…Referring to the method outlined by Sun et al [14], a 500 g PP package containing a mixture of rice bran, ginseng residue, and peanut residue at a ratio of 4:1:1, with a moisture content of 45%, was placed in an autoclave for sterilization at 121 • C for 1 h. Subsequently, 10 mL of preactivated solution of Hericium erinaceus was withdrawn and added into PP package, thoroughly mixed, and then transferred to a 25 • C thermostat incubator for 5-week cultivation period.…”
Section: Preparation Of Pp Package and Cultivation Of Hericium Erinaceusmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidative activity of Hericium erinaceus has been demonstrated in several pre-clinical experimental models of neurodegenerative disorders such as epilepsy, Alzheimer’s disease (AD), traumatic brain injury (TBI), and Parkinson’s disease [ 18 , 19 , 20 ]. Moreover, previous studies on zebrafish embryos have shown the protective and repairing effects of Hericium erinaceus in ethanol-induced neuronal loss [ 21 ]. Zebrafish ( Danio rerio ) has been well accepted as a general fish and vertebrate model to investigate chemical toxicity and the associated mechanisms because of its easy ability to be bread in the laboratory, great fecundity, fast development, short life cycle, and eggs and embryo transparency [ 22 ].…”
Section: Introductionmentioning
confidence: 99%